Colonic mucosa–associated lymphoid tissue lymphoma: A case report - Chen, Dan; Zhong, Ding-Fu; Yang, Yi; Chen, Si-Shuang; Liu, Dong (Frontiers in Surgery, 2023)
Mucosa-associated lymphoid tissue (MALT) lymphoma is a group of extra-nodal lymphomas that originate from B cells. Primary colonic MALT lymphoma is a rare disease, and there is no consensus on its endoscopic features and standard therapies. It is essential to raise awareness of colonic MALT lymphoma, and choose the appropriate treatment.